2019
DOI: 10.1016/j.coastaleng.2019.103533
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automatic detection of the overtopping waves and reconstruction of the overtopping flow characteristics at coastal structures

Abstract: This paper proposes a semi-automatic and customizable procedure for the identification of the overtopping waves based on a threshold-down-crossing analysis of the sea surface elevation signals. The procedure can be applied to 2D experimental and numerical signals, to emerged and submerged structures, with the same accuracy of a human-supervised analysis. The procedure includes an original and innovative algorithm to compare the water level signals at consecutive gauges and couple the waves propagating in betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Formentin and Zanuttigh [23] also developed a semi-automatic procedure including two steps which is applicable for any recorded signal (e.g. overtopping flow thickness, discharge, …) from experimental or numerical tests.…”
Section: Overtopping Event Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formentin and Zanuttigh [23] also developed a semi-automatic procedure including two steps which is applicable for any recorded signal (e.g. overtopping flow thickness, discharge, …) from experimental or numerical tests.…”
Section: Overtopping Event Detectionmentioning
confidence: 99%
“…Whilst the study of wave-by-wave overtopping has increased in recent years e.g. [21][22][23], gaps in knowledge exist in terms of the range of wave-structure parameter combinations that have been studied. Consequently, this paper provides a detailed review of publicly available studies on individual wave overtopping at sea defence structures with the aim of identifying current knowledge gaps to inform future studies.…”
Section: Introductionmentioning
confidence: 99%
“…The Weibull plots of individual overtopping volume can be further analysed to determine the Weibull b parameter (shape parameter in Eq.6) for predicting the maximum overtopping volumes. Previous studies highlighted the changes in the behaviour of Weibull distribution when 'b' parameter is fitted with either upper or lower parts of individual overtopping volumes (Formentin and Zanuttigh, 2019b;Molines et al, 2019b). It was found that fitting the shape parameter b using the highest 10% volumes provides better estimations of the maximum individual overtopping volume, compared to that of highest 50% volumes (Hughes et al, 2012;Zanuttigh et al, 2013).…”
Section: Validations Of Reference Casesmentioning
confidence: 99%
“…The formulations of cu as functions of cot(αoff) further prompted by Bosman et al were fitted again on the values of c instead of u. The wave celerities have been computed using the procedure for the identification and coupling of the overtopping waves developed by references [36,37]. The procedure was applied to the time series of the h-signals registered at D1 and D3, providing as outputs, the time lags for the waves to propagate from D1 and D3.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%